Halliday’s Functional Grammar: Philosophical Foundation and Epistemology - Nguyen Thi Tu Trinh; Phan Van Hoa; Tran Huu Phuc (Humaniora, 2017)
It is difficult to track the philosophy foundation and epistemology of systemic functional grammar (SFG) formulated by Halliday in the 1980s as this kind of grammar views language as a systemic resource for meaning. Besides, it has had global impacts on linguistics and flourished in contemporary linguistic theory. Anyone who is familiar with Halliday’s work realizes that his SFG is an approach designed to analyze English texts. Halliday (1994: xv) explicitly states that “to construct a grammar for purposes of text analysis: one that would make it possible to say sensible and useful things about any text, spoken or written, in modern English.” The aim of this study is not about the applicability of SFG to text analysis as many researchers and scholars do. Our efforts are made to clarify the philosophical foundation of Halliday’s SFG. The paper presents on triangle: (i) language, mind and world; (ii) and empiricism in Halliday’s SFG.